Training and Guidance for the business unit, a village-owned enterprise of Mekar Jaya, Gwinjaya Village, East Bonggo District, Sarmi Regency, Papua Province, in Making Sago Soy Sauce - Gunaedi, Tri; Suyono, Ign Joko; Asnawi, Meinarni (PT Inovasi Pratama Internasional, 2025)
Training and Guidance for the business unit, a village-owned enterprise of Mekar Jaya, Gwinjaya Village, East Bonggo District, Sarmi Regency, Papua Province, in Making Sago Soy Sauce aims to provide skills in making soy sauce with additional nutrition derived from sago flour. Sago flour, in addition to being a nutritional supplement, is also a natural thickener added to sago soy sauce. The activity was carried out by socializing the importance of partnering with academics in producing products and their marketing. In addition, together with the participants, they made sago soy sauce based on the procedures that have been explained, after the sago soy sauce was successfully made, the quality and level of preference were tested with an organoleptic test compared to soy sauce on the market with a Likert scale (very much like, very much like, like, somewhat like, less like, and dislike) with parameters (taste, smell, texture, aroma and color). Additional material in the form of marketing aspects began with determining the cost price and marketing strategies. After participating in the training and guidance, participants were able to make sago soy sauce and were able to determine the cost price. The results of the organoleptic test showed that, on average, the respondents showed a level of liking for the taste, smell, texture, aroma, and color of the sago soy sauce product they produced.